HFpEF in the Elderly: Exercise-Based Immunomodulatory Interventions and New Strategies - Rui Li; Ahmad Rashidi Mohamed Tahir; Shairyzah Ahmad Hisham; Siying Chen (Trends in Immunotherapy, 2026)
To examine the immunopathological mechanisms underlying heart failure with preserved ejection fraction (HFpEF) in elderly patients and evaluate exercise training as an immunomodulatory intervention for managing disease complications. A narrative literature review was conducted using PubMed, Embase, and Cochrane Library databases (2010–2023), focusing on immune dysfunction, aging, and exercise interventions in HFpEF. HFpEF pathophysiology in elderly patients involves complex interactions between innate and adaptive immunity, characterized by elevated pro-inflammatory cytokines, NLRP3 inflammasome activation, and immune cell dysfunction. Major complications—frailty syndrome, sarcopenia, and malnutrition—share common inflammatory pathways that perpetuate disease progression. Exercise training fundamentally alters this inflammatory profile through multiple mechanisms: suppressing pro-inflammatory cytokine production (TNF-α, IL-1β, IL-6), promoting anti-inflammatory immune cell phenotypes, and enhancing tissue regenerative capacity. Unlike pharmacological interventions targeting single pathways, exercise exerts pleiotropic effects across the immune-inflammatory network, simultaneously addressing cardiac dysfunction and systemic complications. Structured exercise programs effectively interrupt inflammatory cascades, improve functional capacity, and enhance quality of life in elderly HFpEF patients. Exercise training represents a cornerstone intervention that directly targets the fundamental immunopathology of HFpEF. Implementation of specialized exercise-based cardiac rehabilitation programs tailored to elderly patients is urgently needed to optimize clinical outcomes in this growing population.